Designing of buildings and structures at land sliding and slide hazardous segments of slopes - Slyusarenko, Yuriy; Tytarenko, Volodymyr; Shuminskiy, Valerii; Vynnykov, Yuriy (Academic journal Industrial Machine Building Civil Engineering, 2018)
The main document of the regulatory framework for the design of buildings and structures on landslide and landslide-prone areas is DBN.1.1-46:2017 «Engineering protection of territories, buildings and structures from landslides and landslides. The main provisions» and the state standard DSTU-N B V.1.1-37:2016, «Manual on engineering protection of territories, buildings and structures from landslides and landslips». In development of the provisions of this set of regulatory framework, a number of regulations and standards have been developed to ensure the construction of buildings and structures on landslide and landslide-prone areas, considering the complex geological and hydro geological conditions of the construction site.